2008
DOI: 10.1017/s0033291708004704
|View full text |Cite
|
Sign up to set email alerts
|

The influence of emotion clarity on emotional prosody identification in paranoid schizophrenia

Abstract: Background. Identification of emotional facial expression and emotional prosody (i.e. speech melody) is often impaired in schizophrenia. For facial emotion identification, a recent study suggested that the relative deficit in schizophrenia is enhanced when the presented emotion is easier to recognize. It is unclear whether this effect is specific to face processing or part of a more general emotion recognition deficit.Method. We used clarity-graded emotional prosodic stimuli without semantic content, and teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 28 publications
1
50
1
Order By: Relevance
“…We have argued that this could be due to enhanced noise in respective neural structures: This deficit is more pronounced for clear than for more ambiguous emotional stimuli both in the visual 37 and auditory 28 domain, as would be expected under this hypothesis. 28 Such a mechanism could also explain the present results. However, one would need to rule out some alternative explanations discussed above, such as deficits in static intensity perception or in sound source localization based on intensity.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…We have argued that this could be due to enhanced noise in respective neural structures: This deficit is more pronounced for clear than for more ambiguous emotional stimuli both in the visual 37 and auditory 28 domain, as would be expected under this hypothesis. 28 Such a mechanism could also explain the present results. However, one would need to rule out some alternative explanations discussed above, such as deficits in static intensity perception or in sound source localization based on intensity.…”
Section: Discussionmentioning
confidence: 69%
“…Also, there is evidence that the prosody perception deficit in schizophrenia covaries with an impairment to extract emotional information from facial expression, 7,8,28,36 pointing toward a more general deficit in the extraction of emotional meaning from sensory information. We have argued that this could be due to enhanced noise in respective neural structures: This deficit is more pronounced for clear than for more ambiguous emotional stimuli both in the visual 37 and auditory 28 domain, as would be expected under this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, clarity is fundamental to the perception of facial expressions as well as to achieve mutual adjustment between people (e.g., Bach, Buxtorf, Grandjean, & Strik, 2009). Clarity has also been defined as referring to the reliability of the signal that permits a quick, accurate and efficient recognition of a facial expression (e.g., Tracy & Robins, 2008).…”
Section: Dimensions Of Interestmentioning
confidence: 99%
“…Clarity has also been defined as referring to the reliability of the signal that permits a quick, accurate and efficient recognition of a facial expression (e.g., Tracy & Robins, 2008). Clarity is therefore often inferred from the capability for accurately identifying the emotions (Bach et al, 2009). Some studies have shown that clarity judgments depend on whether the expression of a specific emotion is genuine or simulated (Gosselin, Kirouac, & Doré, 2005).…”
Section: Dimensions Of Interestmentioning
confidence: 99%